The care of adults with congenital heart disease across the globe: Current assessment and future perspective: A position statement from the International Society for Adult Congenital Heart Disease (ISACHD). (15th September 2015) - Webb, Gary; Mulder, Barbara J.; Aboulhosn, Jamil; Daniels, Curt J.; Elizari, Maria Amalia; Hong, Gu; Horlick, Eric; Landzberg, Michael J.; Marelli, Ariane J.; O'Donnell, Clare P.; Oechslin, Erwin N.; Pearson, Dorothy D.; et al.
Abstract: The number of adults with congenital heart disease (CHD) has increased markedly over the past few decades as a result of astounding successes in pediatric cardiac care. Nevertheless, it is now well understood that CHD is not cured but palliated, such that life-long expert care is required to optimize outcomes. All countries in the world that experience improved survival in CHD must face new challenges inherent to the emergence of a growing and aging CHD population with changing needs and medical and psychosocial issues. Founded in 1992, the International Society for Adult Congenital Heart Disease (ISACHD) is the leading global organization of professionals dedicated to pursuing excellence in the care of adults with CHD worldwide. Recognizing the unique and varied issues involved in caring for adults with CHD, ISACHD established a task force to assess the current status of care for adults with CHD across the globe, highlight major challenges and priorities, and provide future direction. The writing committee consisted of experts from North America, South America, Europe, South Asia, East Asia, and Oceania. The committee was divided into subgroups to review key aspects of adult CHD (ACHD) care. Regional representatives were tasked with investigating and reporting on relevant local issues as accurately as possible, within the constraints of available data. The resulting ISACHD position statement addresses changing patterns of worldwide epidemiology, models of care and organization of care, education and training, and the global research landscape in ACHD. Highlights: An ISACHD taskforce assessed the status of ACHD care across the world. Experts from North/South America, Europe, South/East Asia and Oceania were convened. The position statement addresses changing patterns of worldwide epidemiology. Models and organization of ACHD care, education, training and research are explored. Major challenges and priorities are highlighted and future direction is provided.